Malignant Hyperthermia During Translabyrinthine Acoustic Neuroma Surgery After Previous Uneventful Surgery. Issue 6 (July 2019) - Erbele, Isaac; Chapman, Eric; Wilson, Meghan N.; Arriaga, Moises A.
Abstract : Objective: Review current literature and guidelines for malignant hyperthermia in the context of neurotologic surgery. Patient: A case of malignant hyperthermia during vestibular schwannoma surgery, in a patient previously exposed to anesthesia. Interventions: Excision of vestibular schwannoma, acute management of malignant hyperthermia. Main Outcome Measures: Knowledge of the basic pathophysiology, clinical manifestations, and treatment protocols for malignant hyperthermia. Results: Rapid termination of the procedure and appropriate modifications in surgical technique permitted expeditious treatment of malignant hyperthermia and prevented its lethality. Conclusions: Malignant hyperthermia is a rare and lethal condition that may arise in neurotologic surgery, even in patients who have previously received general anesthesia. The neurotologic surgeon has a role in early recognition and expeditious termination of surgery to help reduce its mortality.